Fiscal Stimulus with Spending Reversals - Muller, Gernot (IMF Working Papers; Working Paper, 2009)
The impact of fiscal stimulus depends not only on short-term tax and spending policies, but also on expectations about offsetting measures in the future. This paper analyzes the effects of an increase in government spending under a plausible debt-stabilizing policy that links current stimulus to a subsequent period of spending restraint. Accounting for such spending reversals brings an otherwise standard new Keynesian model in line with the stylized facts of fiscal transmission, including the crowding-in of consumption and the 'puzzle' of real exchange rate depreciation. Time series evidence for the U.S. supports the empirical relevance of spending reversals.